Prognostic value of 8F-Florbetapir scan: a 36-month follow up analysis using ADNI data. (3rd June 2015) - Lu, M; Pontecorvo, M; Siderowf, A; Joshi, AD; Devous, MD; Mintun, MA; Montoya, A
Abstract : Background: The Alzheimer's Disease Neuroimaging Initiative (ADNI) provides an opportunity to investigate the relationship between β-Amyloid neuropathology and patients' long-term cognitive function change. We examined baseline 18F-florbetapir PET amyloid imaging status and 36-months' change from baseline in cognitive performance in subjects with mild cognitive impairment (MCI). Method: The study included all ADNI subjects who underwent PET-imaging with 18F-florbetapir and had a clinical diagnosis of MCI at the visit closest to florbetapir imaging. β-Amyloid deposition was measured by florbetapir standard uptake value ratio (SUVR), and dichotomized as Aβ+(SUVR>1.1) or Aβ–(SUVR≤1.1). Cognitive scores, including ADAS11, MMSE and CDR sum of boxes (CDR-SB), were evaluated for up to 36 months. Results: Of 478 MCI-subjects who had at least one florbetapir scan, 153 had a cognitive evaluation at 36-month follow-up. Of those, 79 were Aβ– and 74 Aβ+. At 36-months, the Aβ+ vs. Aβ– group scores changed from baseline (LS means 4.03 vs. 0.26 for ADAS11; -2.61 vs.-0.40 for MMSE; 1.53 vs. -0.11 for CDR-SB [p< 0.0001 all comparisons]). Generalised estimating equation analysis on clinically significant cognitive change showed a marginal Odds Ratio=2.18 (95% CI: 1.47–3.21) for Aβ+ vs. Aβ– groups. Conclusion: MCI subjects with higher β-Amyloid deposition had greater deterioration in cognitive function over 36 months while subjects with no β-Amyloid accumulation tended to be stable.